Aktivitas dan Perilaku Pasangan Owa Jawa (Hylobates moloch) di Javan Gibbon Centre - Muhamad Ilham; Dyah Perwitasari Farajallah; Entang Iskandar (Jurnal Ilmu Pertanian Indonesia, 2019)
Since 2008 Javan Gibbon’s (Hylobates moloch) status is endangered due to the capture of gibbons in the wild to be used as pets which are increasingly prevalent. Conservation efforts of Javan Gibbon population have been conducted at the rescue populations of Javan Gibbons in Javan Gibbon Centre (JGC). Javan Gibbon are the result of voluntary surrender of the community and confiscation of quarantine officer. Rehabilitation in JGC aims to restore the wild instincts of Javan Gibbon before being released in to the wild environment. This study aimed to identify the daily activities and behavior patterns of Javan gibbon pair and to analyze the abiotic factors that influence them in Javan Gibbon Centre (JGC) as one aspect of their readiness to be released into the wild environment. The study focused on three pairs of Javan Gibbons namely Boby-Jolly, Willie-Sasa, and Asep-Dompu. Based on the observation of three pairs of Javan gibbon, resting is the most dominant activity with the percentage of 60-80% followed by traveling (8-20%), feeding (7-13%), social (0-4%), and aggressive behavior (<1%). The most common social behaviors of Javan Gibbon pairs were allogrooming, courtship, and vocalization. Ambient temperature and rainfall were abiotics factors the most affecting the activity and behavior of the Javan Gibbon pair in terms of vocalization. Javan Gibbon will stop vocalization if the ambient temperature is low and when rainfall is high. Based on the observation data, Willie-Sasa was considered to have fulfilled one aspect of the assessment for their release into the wild environment. The dominant aspect of this pair is the frequency of socialization and vocalization that approaches frequency of Javan Gibbon behavior in the wild environment.